Catalyst for hydrogen production through ammonia decomposition under mild condition as well as preparation and application of catalyst
By using magnesium oxide as a support in the ammonia decomposition hydrogen production catalyst, the combination of Ru, MgO, SiO2 and other components is formed, which solves the problem of weak activity and poor stability of the catalyst under low temperature conditions, and achieves efficient ammonia decomposition hydrogen production effect, and has the potential for industrial application.
Patent Information
- Application Number
- CN202510114016.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-15
AI Technical Summary
The existing ammonia decomposition hydrogen production catalysts have weak activity, poor stability, and difficult to form under low temperature conditions. The preparation process is complex and the energy consumption is high, making it difficult to achieve industrial application.
The ammonia decomposition hydrogen production catalyst with magnesium oxide as a support, Ru, MgO, SiO2 and other components is used to form a highly dispersible Ru atom pair through efficient stirring and molding additives, thereby improving catalytic activity and stability.
Within the range of 400-600°C, the ammonia decomposition efficiency of the catalyst reaches more than 99%, with excellent catalytic performance and industrial production potential, reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for producing hydrogen by decomposing ammonia and its preparation and application, belonging to the field of energy catalysis. Background Art
[0002] Hydrogen energy is widely studied and applied as an efficient green energy. In recent years, with the large-scale use of hydrogen as energy in small hydrogen refueling stations, petrochemicals, and metallurgy, a green and low-carbon chemical industry chain is being formed. However, the storage and transportation conditions of hydrogen are harsh, and the use of hydrogen storage carriers is an effective means of achieving hydrogen storage and transportation. How to efficiently produce hydrogen is the key link in the large-scale application of hydrogen energy.
[0003] Ammonia is a basic chemical raw material, widely used in fertilizers, environmental protection and other fields. Ammonia is also a high-density hydrogen storage carrier (17.3wt% hydrogen content), with advantages such as low storage and transportation costs, safety and high efficiency. In addition, the use of ammonia catalytic decomposition to produce hydrogen has significant advantages such as zero carbon emissions, and is an important way for the development of the green hydrogen energy industry. However, the operating temperature of existing industrial ammonia decomposition hydrogen production catalysts is 800-900℃, and the energy consumption is high. The research and development of ammonia decomposition hydrogen production catalysts under mild conditions is the current focus of green energy conversion.
[0004] Ni-based catalysts are usually used in existing industrial ammonia catalytic decomposition hydrogen production devices, which have problems such as high reaction temperature and low ammonia decomposition efficiency. It is urgent to develop a new ammonia decomposition hydrogen production catalyst system to make up for these shortcomings. Precious metal catalysts such as Ru, Ir, and Pt have the characteristics of high conversion rate and good stability at relatively low temperatures, and have good application prospects. However, existing precious metal catalysts have problems such as high precious metal content and high cost. At present, many scholars at home and abroad have conducted research on ammonia decomposition catalysts, and their research focus is on reducing the operating temperature range and improving the ammonia decomposition efficiency.
[0005] CN 116550325 A discloses an ammonia decomposition hydrogen production catalyst and its preparation method. A coprecipitation method is used to synthesize an iron-magnesium-aluminum hydrotalcite precursor, which is calcined and decomposed in an air atmosphere to obtain a magnesium-aluminum-iron oxide, and then reduced to generate a magnesium-aluminum-iron catalyst. In the invention, the average grain size of α-Fe is 14.8-20.9nm, and after the ammonia decomposition reaction, α-Fe undergoes nitridation and is completely converted into FeN, with an average grain size of 10.7-16.4nm. The specific surface area of the catalyst is increased by doping with Al, which helps to disperse the Fe metal in the catalyst, thereby improving the catalytic activity of the catalyst. The ammonia decomposition efficiency is 90% at 650°C, but the catalyst preparation process is complicated and the energy consumption is high.
[0006] CN 111215086 A discloses the use of a rare earth oxide supported transition metal catalyst in ammonia decomposition reaction. The catalyst is prepared by a deposition precipitation method, and the product is washed, dried, and reduced to obtain a rare earth metal oxide supported transition metal catalyst. The preparation method of the invention is simple, and the inexpensive transition metal is used as the active metal, so the cost is low. However, the ammonia decomposition efficiency is only 88.2% at 600°C.
[0007] CN 112337494 A discloses a catalyst for hydrogen production by decomposing ammonia, and its preparation method and application. The catalyst is prepared by a sol-gel method, and includes a non-precious metal active component and a BN-rare earth metal oxide composite carrier loaded with the non-precious metal active component. The mass fraction of the active components Ni and Co in the catalyst is 5-20wt%, and the mass fraction of the carrier is 80-95wt%. The catalyst preparation process of the invention is simple, but the ammonia conversion rate is only 96.1% at 650°C, indicating that the catalyst has a high ammonia decomposition conversion temperature and a low decomposition efficiency.
[0008] In summary, non-precious metal ammonia decomposition catalysts are mainly Ni, Co, Fe and rare earth metal oxides, and the reaction temperature is as high as 600°C or above, which makes it difficult to effectively solve the problem of high energy consumption of ammonia decomposition hydrogen production equipment. In recent years, precious metal ruthenium-based catalysts have been widely studied and reported due to their excellent ammonia decomposition performance.
[0009] CN 108160072 A discloses a method for preparing a magnesium oxide supported ruthenium catalyst for ammonia decomposition and hydrogen production and its application. The catalyst uses magnesium oxide as a carrier and metallic ruthenium as an active ingredient. Ruthenium particles are uniformly dispersed on the surface of magnesium oxide, wherein the ruthenium content accounts for 0.5-10wt.% of the total weight of the catalyst. The invention uses a deposition precipitation method to prepare a magnesium oxide supported ruthenium catalyst precursor, and the obtained product is washed, dried, and then reduced in a reducing atmosphere to prepare a magnesium oxide supported ruthenium catalyst with highly dispersed ruthenium. The invention has a simple method for preparing the catalyst, and the prepared ruthenium catalyst has the advantages of good metal dispersion, etc., but the catalyst produced by this method has an unsatisfactory ammonia decomposition efficiency.
[0010] CN 113058595 A discloses a ruthenium-based ammonia decomposition hydrogen production catalyst and its preparation method. The preparation method is a colloidal precipitation method, wherein a ruthenium metal salt is dispersed in an alcohol solvent, and an alkaline solution is added thereto to react at a certain temperature to obtain a ruthenium colloid. Zirconium dioxide, cerium dioxide, aluminum oxide, and magnesium oxide metal oxide carriers are dispersed in an aqueous solution, and a certain amount of ruthenium colloid is added. After stirring, drying, roasting and molding, a supported metal ruthenium catalyst is obtained. Zirconium dioxide, cerium dioxide, aluminum oxide, and magnesium oxide use ruthenium colloid as a precursor and are loaded on a metal oxide carrier. The interaction between ruthenium and the carrier is enhanced, and the obtained catalyst ruthenium microcrystals are in a highly dispersed state. The catalytic efficiency of ammonia decomposition hydrogen production at 530°C is 95%. The catalyst preparation process is complicated and difficult to industrialize.
[0011] CN 114471553 A discloses the preparation and application of a rare earth modified catalyst for ammonia decomposition to produce hydrogen. Yttrium and potassium are used as catalyst additives, and the use of precious metal ruthenium is reduced by using γ-alumina as a carrier and coordinating with yttrium and potassium. The patent effectively inhibits H poisoning of ruthenium species and reduces the apparent activation energy. The preparation method of the present invention is simple and easy, the prepared catalyst has high catalytic activity, the cost is lower than other ruthenium-based catalysts, and the ammonia decomposition efficiency at 430°C is 86.7%. However, the active species ruthenium in the patent is easy to agglomerate and difficult to operate for a long time.
[0012] CN 109529865 A discloses a ruthenium-based ammonia decomposition hydrogen production catalyst, wherein the active component is ruthenium, the promoter is cesium and / or potassium, and the carrier includes magnesium oxide, activated carbon, cerium oxide, molybdenum oxide, tungsten oxide, barium oxide and potassium oxide. Epoxy resin is added as a binder for molding, and finally, the reduced molded product is calcined at high temperature (1900-2000°C) to obtain a ruthenium-based ammonia decomposition hydrogen production catalyst. The ammonia decomposition efficiency is 95% at 450°C, and it has good activity. However, the calcination temperature in this process is too high, and industrialization is difficult.
[0013] CN110270338 A discloses a nickel and / or ruthenium-based ammonia decomposition catalyst and its preparation method and application. The active component is one or both of nickel and ruthenium, and the carrier is graphitized activated carbon and an auxiliary agent. The auxiliary agent is one or more of alkali metal oxides and carbonates, alkaline earth metal oxides and carbonates, and rare earth oxides. The invention graphitizes the activated carbon at high temperature (1200-2000°C), which improves the stability of the catalyst on the one hand, and forms a strong interaction between the active component and the carrier carbon on the other hand, resulting in electron transfer, which is beneficial to the desorption of the reaction products N and H, further improving its low-temperature reaction activity, achieving a better ammonia decomposition effect, and improving the ammonia treatment efficiency. The ammonia decomposition efficiency at 550°C is 92.7%. The catalyst carrier activated carbon needs to be subjected to a high temperature of more than 1200°C, and industrial continuous production is difficult.
[0014] In summary, although the ruthenium-based ammonia decomposition hydrogen production catalysts reported in existing patents have good catalytic performance, the catalyst preparation process steps are complicated, and the heating temperature during the preparation of some catalysts is too high, which cannot be realized in industrial application. It is urgent to develop high-performance ruthenium-based catalysts that can be industrially produced. Summary of the invention
[0015] In view of this, the purpose of the present invention is to disclose a catalyst for hydrogen production by decomposing ammonia under mild conditions and a preparation method thereof, aiming to solve the problems of weak activity, poor stability and difficulty in molding of existing catalysts for hydrogen production by decomposing ammonia under low temperature conditions.
[0016] 1. Catalyst for hydrogen production by decomposition of ammonia and its preparation The catalyst for hydrogen production by decomposing ammonia under mild conditions of the present invention comprises the following components in percentage by weight: MgO 55-99.87%, Ru 0.1-5% and SiO2 0.01-5%, and one or more of the following metal components: Me1 0.1-25% and Me2 0.02-10%.
[0017] The Me1 is one or more of lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, ytterbium, molybdenum, iron, cobalt and nickel, and the Me2 is one or more of lithium, sodium, potassium, rubidium and cesium.
[0018] The method for preparing the catalyst for hydrogen production by decomposing ammonia under mild conditions of the present invention comprises the following steps: (1) Adding a ruthenium salt into distilled water to dissolve it to form a solution A; the amount of the ruthenium salt added is 0.1-5% of the total mass of the catalyst, measured as ruthenium; the ruthenium salt is at least one of ruthenium trichloride or ruthenium nitrate.
[0019] (2) dissolving at least one of a transition metal precursor or a rare earth metal precursor in distilled water to form a solution B; the amount of the metal precursor added is 0.1-25% of the total mass of the catalyst, measured by mass of metal Me1; the transition metal precursor is at least one of a molybdenum salt, an iron salt, a cobalt salt and a nickel salt, and the rare earth metal precursor is at least one of a lanthanum salt, a cerium salt, a praseodymium salt, a neodymium salt, a samarium salt, a gadolinium salt and a ytterbium salt.
[0020] (3) dissolving an alkali metal precursor in distilled water to form a solution C; the amount of the alkali metal precursor added is 0.02-10% of the total mass of the catalyst, measured by mass of metal Me2; the alkali metal precursor is at least one of a lithium salt, a sodium salt, a potassium salt, a rubidium salt and a cesium salt.
[0021] (4) adding part of the (111) face-rich octahedral magnesium oxide powder, a binder and a pore-forming agent into a mixer, and then adding water, and stirring at high speed for 3-60 minutes; then slowly adding solution A into the mixer, and stirring at high speed for 10-120 minutes; then adding at least one of solution B or solution C and a molding aid, and stirring at high speed for 10-120 minutes; adding the remaining octahedral magnesium oxide powder again, stirring at high speed for 10-120 minutes, controlling the moisture content at 25-35%, and finally filtering and vacuum kneading to obtain a plastic clay material, and then aging it at a temperature of 10-30°C and a humidity of 60-70% for 24h-48h; extruding the aged plastic clay material into a Raschig ring, a cloverleaf or a cylindrical embryo through an extruder, and drying and calcining to obtain the ammonia decomposition hydrogen production catalyst; The binder is at least one of hydroxypropyl methylcellulose, hydroxyethyl cellulose or carboxymethyl cellulose, and the amount is 0.1-3% of the dry weight of the octahedral magnesium oxide powder; the pore-forming agent is at least one of polyethylene oxide, polyvinyl alcohol, methyl methacrylate or polystyrene, and the amount is 0.1-2% of the total mass of the catalyst; the molding aids are glass fiber, pulp fiber and lactic acid, and the amounts are 0.01-5%, 0.1-1.5% and 0.1-3% of the total mass of the catalyst respectively. The drying environment temperature is 20-60℃, the humidity is 85-10%, and it gradually changes from low temperature and high humidity to high temperature and low humidity. The drying time is 8-9 days; the calcination adopts a continuous mesh belt kiln, the calcination temperature is 300-650℃, the product kiln temperature is 60-80℃, and the roasting time is controlled at 40-48h.
[0022] The precursors of metals such as ruthenium, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, ytterbium, molybdenum, iron, cobalt, lithium, sodium, potassium, rubidium, and cesium in the present invention are all commonly used raw materials for preparing industrial catalysts in the prior art. The technical indicators and usage of the raw materials can be selected according to the actual process conditions and equipment characteristics. Among them, inorganic salts or carbonyl metal compounds are preferably used for transition metals and rare earth metals, and strong base salts such as hydroxides and alcoholates are preferably used for alkali metals.
[0023] The application of the catalyst for hydrogen production by decomposing ammonia under mild conditions of the present invention is specifically described as follows: after the catalyst for hydrogen production by decomposing ammonia is filled into a reactor, an inert gas is first used to completely purge and remove oxygen in the reaction device and the catalyst pores; secondly, a reducing gas: hydrogen or ammonia is introduced, and the temperature is increased in a stepwise manner for reduction, and the final reduction temperature is 400-650° C. The reduction time is related to the catalyst filling mass, generally 0.1-6 h / kg. After the reduction stage is completed, a reaction raw material gas: ammonia is introduced to carry out a hydrogen production reaction.
[0024] 2. Activity Evaluation of Catalysts for Hydrogen Production from Ammonia Decomposition 1. Evaluation method: Based on the Chemical Industry Standard of the People's Republic of China HG / T 5316-2018 "Test Method for Activity of Ammonia Cracking Hydrogen Production Catalyst". Take the monolithic catalyst sample and calculate it by volume. The reaction conditions are: NH3, space velocity 5000 h -1 The reaction activity of the catalyst is determined by the NH3 conversion (decomposition) rate, and the product is analyzed by gas chromatography.
[0025] 2. Evaluation results: The integral ammonia decomposition hydrogen production catalyst produced by the present invention has an NH3 conversion rate of higher than 99% within the operating temperature range of 400-600°C, and can be widely used in various ammonia decomposition hydrogen production fields.
[0026] Compared with the prior art, the present invention has the following advantages: (1) The preparation method of magnesium oxide as a catalyst carrier for hydrogen production by decomposition of ammonia under mild conditions is simple. The use of magnesium oxide with a high-energy surface (111) greatly promotes the adsorption and activation of ammonia species. The active species ruthenium is easily anchored on the surface of magnesium oxide with a (111) surface in the form of atomic pairs, which greatly promotes the dispersion of ruthenium species and improves the activity of the catalyst. (2) Use some metal atomic clusters to improve the stability of the active species ruthenium species and reduce the key rate-determining step reaction energy barrier. Transition metals such as molybdenum, iron, cobalt, and nickel species, rare earth metals such as lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, ytterbium species, and alkali metals such as lithium, sodium, potassium, rubidium, and cesium species are loaded on the (111) surface of magnesium oxide in the form of atomic clusters. On the one hand, the stability of Ru atomic pairs is improved. On the other hand, these metal atomic clusters can provide abundant electrons for Ru atomic pairs, further improving the efficiency of ruthenium species for NH cleavage activation reaction, greatly reducing the key rate-determining step NH cleavage reaction energy barrier; (3) By constructing Ru atomic pairs, the rate-controlling step of ammonia decomposition, the rate of N atom recombination desorption, is greatly improved; the noble metal Ru species is dispersed on the support surface in the form of atomic pairs, forming [Ru 2+ -O 2− ] ion pairs, forming a supporting interface for the heterogeneous decomposition of NH bonds; the activated protons are rapidly transferred to form product hydrogen and released on the (111) surface of magnesium oxide; at the same time, the Ru atom pairs are electron-enriched, causing the Ru-N antibonding orbit to weaken rapidly, and the recombination of N atoms between the Ru atom pairs to N2 increases the rate-controlling step of ammonia decomposition, the rate of N atom recombination desorption; (4) The catalyst for hydrogen production from ammonia decomposition under mild conditions prepared by this method has high molding efficiency, and its shape and size can be adjusted according to the requirements of the reactor; the preparation process is simple, the industrial continuous efficiency is high, and the production cost is greatly reduced. In addition, the catalyst has high ammonia decomposition efficiency and long service life, and is an original innovative technology for my country's green hydrogen industry. DETAILED DESCRIPTION
[0027] The catalyst for hydrogen production by decomposing ammonia under mild conditions of the present invention, its preparation and application, and catalyst performance are further described below through specific examples.
[0028] Example 1 72.6 kg of ruthenium trichloride was added to 120.0 kg of water to dissolve and form a mixed solution A; 89.63 kg of sodium molybdate was dissolved in 120.0 kg of distilled water to form a mixed solution B; 2.36 kg of sodium sulfate was dissolved in 7.26 kg of distilled water to form a mixed solution C; 272.0 kg of (111) MgO powder, 1.3 kg of carboxymethyl cellulose and 0.2 kg of methyl methacrylate were added to 11.36 kg of deionized water and stirred at high speed for 35 minutes; the mixed solution of A and B was slowly added to the mixer and stirred at high speed for 42 minutes; then C solution, 2.6 kg of glass fiber, 1.1 kg of pulp fiber and 2.1 kg of lactic acid were added in turn and stirred at high speed for 36 minutes; the remaining 408.0 kg of (111) MgO powder and 216.25 kg of distilled water were added again and stirred at high speed for 44 minutes, and the moisture content was controlled at 28%. Finally, the plastic mud was obtained after filtration and vacuum kneading. Aged for 24 hours at a temperature of 15°C and a humidity of 68%. The aged plastic clay was extruded into a Raschig ring-shaped embryo through an extruder. The drying environment temperature was 45°C and the humidity was 75%, gradually changing from low temperature and high humidity to high temperature and low humidity. The drying time was 9 days. Calcination was carried out in a continuous mesh belt kiln, the calcination temperature was 520°C, the product kiln temperature was 75°C, and the roasting time was controlled at 48h. Finally, it was cut into 4mm Raschig rings according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions was obtained, which was recorded as CAT-1. After the catalyst was filled into the reactor, the reaction device was first purged with high-purity nitrogen for 20 hours; secondly, hydrogen was introduced, and the temperature was stepped up (50°C as the first step) for reduction. The final reduction temperature was 510°C, and the reduction was 202h. The reaction gas ammonia was introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0029] Example 2 102.59 kg of ruthenium trichloride was added to 100.0 kg of water to dissolve to form a mixed solution A; 62.35 kg of lanthanum nitrate hexahydrate, 61.99 kg of cerium nitrate hexahydrate, 61.75 kg of praseodymium nitrate hexahydrate, 60.80 kg of neodymium nitrate hexahydrate, 59.11 kg of samarium nitrate hexahydrate, 57.39 kg of gadolinium nitrate hexahydrate, 54.01 kg of ytterbium nitrate hexahydrate, 55.21 kg of ammonium heptamolybdate, 217.01 kg of ferric nitrate nonahydrate, 98.77 kg of cobalt nitrate hexahydrate, and 148.54 kg of nickel nitrate hexahydrate were dissolved in 1200.0 kg of distilled water to form a mixed solution B; 6.90 kg of lithium hydroxide, 3.48 kg of sodium hydroxide, 2.87 kg of hydrogen Potassium oxide, 2.40kg rubidium hydroxide, and 2.26kg cesium hydroxide were dissolved in 35.0kg distilled water to form a mixed solution C; 165.0kg (111)-face magnesium oxide powder, 1.0kg hydroxypropyl methylcellulose, 1.0kg hydroxyethyl cellulose, 1.0kg carboxymethyl cellulose, 0.5kg polyethylene oxide, 0.5kg polyvinyl alcohol, 0.5kg methyl methacrylate, and 0.5kg polystyrene were added to 63.24kg deionized water and stirred at high speed for 30min; then the mixed solution of A and B was slowly added to the mixer and stirred at high speed for 120min; then C solution, 5.0kg glass fiber, 1.5kg pulp fiber, and 3.0kg lactic acid were added in sequence and stirred at high speed for 120min; the remaining 385.0kg (111)-face magnesium oxide powder and 106.32kg distilled water were added again and stirred at high speed for 120min, and the moisture content was controlled at 35%. Finally, the plastic mud was obtained after filtration and vacuum kneading. Aged for 24 hours at a temperature of 10°C and a humidity of 70%. The aged plastic clay was extruded into Raschig rings through an extruder. The drying environment temperature was 30°C and the humidity was 70%. It gradually changed from low temperature and high humidity to high temperature and low humidity. The drying time was 9 days. Calcination was carried out in a continuous mesh belt kiln. The calcination temperature was 650°C, the product kiln temperature was 80°C, and the roasting time was controlled at 48 hours. Finally, it was cut into 3mm Raschig rings according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions was obtained, which was recorded as CAT-2. After the catalyst was filled into the reactor, the reaction device was first purged with high-purity nitrogen for 20 hours; secondly, ammonia was introduced, and the temperature was reduced in a step-by-step manner. The final reduction temperature was 650°C, and the reduction was 167 hours. The reaction gas ammonia was introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0030] Example 3 53.42 kg of ruthenium nitrate was added to 160.0 kg of water to dissolve and form a mixed solution A; 72.16 kg of cerium sulfate was dissolved in 130.0 kg of distilled water to form a mixed solution B; 4.32 kg of sodium carbonate was dissolved in 5.0 kg of distilled water to form a mixed solution C; 244.8 kg of (111)-face magnesium oxide powder, 1.8 kg of hydroxyethyl cellulose, and 0.8 kg of polyvinyl alcohol were added to 106.32 kg of deionized water and stirred at high speed for 15 minutes; then the mixed solution of A and B was slowly added to the mixer and stirred at high speed for 40 minutes; then C solution, 3.2 kg of glass fiber, 0.8 kg of pulp fiber and 0.6 kg of lactic acid were added in sequence and stirred at high speed for 30 minutes; the remaining 367.2 kg of (111)-face magnesium oxide powder and 374.32 kg of distilled water were added again and stirred at high speed for 36 minutes, and the moisture content was controlled at 25%. Finally, the plastic mud was obtained after filtration and vacuum kneading. Aged for 26 hours at a temperature of 20°C and a humidity of 65%. The aged plastic clay was extruded into a clover-type embryo through an extruder. The drying environment temperature was 35°C and the humidity was 65%, gradually changing from low temperature and high humidity to high temperature and low humidity. The drying time was 9 days. Calcination was carried out in a continuous mesh belt kiln, the calcination temperature was 550°C, the product kiln temperature was 70°C, and the roasting time was controlled at 36 hours. Finally, it was cut into 4mm clover according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions was obtained, which was recorded as CAT-3. After the catalyst was filled into the reactor, the reaction device was first purged with high-purity nitrogen for 24 hours; secondly, hydrogen was introduced, and the temperature was reduced in a step-by-step manner. The final reduction temperature was 500°C, and the reduction was 240 hours. The reaction gas ammonia was introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0031] Example 4 2.05 kg of ruthenium trichloride was dissolved in 100 kg of water to form a mixed solution A; 0.69 kg of lithium hydroxide was dissolved in 7.2 kg of distilled water to form a mixed solution C; 299.61 kg of (111) MgO powder, 1.0 kg of hydroxypropyl methylcellulose, and 1.0 kg of polyethylene oxide were added to 119.72 kg of deionized water and stirred at high speed for 3 minutes; then the A solution was slowly added to the mixer and stirred at high speed for 10 minutes; then the C solution, 0.01 kg of glass fiber, 0.1 kg of pulp fiber and 0.1 kg of lactic acid were added and stirred at high speed for 10 minutes; the remaining 699.09 kg of (111) MgO powder and 279.36 kg of distilled water were added again and stirred at high speed for 10 minutes, and the water content was controlled at 35%. Finally, the plastic clay was obtained after filtration and vacuum kneading. Aged for 24 hours at a temperature of 10 ° C and a humidity of 60%. The aged plastic clay is extruded into Raschig rings through an extruder. The drying environment temperature is 20°C and the humidity is 85%. It gradually changes from low temperature and high humidity to high temperature and low humidity. The drying time is 8 days. The calcination adopts a continuous mesh belt kiln, the calcination temperature is 300°C, the product kiln temperature is 60°C, and the roasting time is controlled at 40h. Finally, it is cut into 5mm Raschig ring-shaped embryos according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions is obtained, which is recorded as CAT-4. After the catalyst is filled into the reactor, the reaction device is first purged with high-purity nitrogen for 20h; secondly, ammonia is introduced, and the temperature is reduced in a step-by-step manner. The final reduction temperature is 400°C, and the reduction is 200h. The reaction gas ammonia is introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0032] Example 5 63.21 kg of ruthenium nitrate was added to 126.0 kg of water to dissolve and form a mixed solution A; 216.3 kg of cerium carbonate was dissolved in 410.0 kg of distilled water to form a mixed solution B; 3.16 kg of cesium hydroxide was dissolved in 20.0 kg of distilled water to form a mixed solution C; 276.0 kg of (111) magnesium oxide powder, 0.8 kg of carboxymethyl cellulose and 0.2 kg of polystyrene were added to 12.42 kg of deionized water and stirred at high speed for 36 minutes; the mixed solution of A and B was slowly added to the mixer and stirred at high speed for 40 minutes; then 3.5 kg of glass fiber, 1.1 kg of pulp fiber and 1.6 kg of lactic acid were stirred at high speed for 36 minutes; the remaining 414.0 kg of (111) magnesium oxide powder and 223.63 kg of distilled water were added again and stirred at high speed for 45 minutes, and the moisture content was controlled at 29%. Finally, the plastic mud was obtained after filtration and vacuum kneading. Aged for 32 hours at a temperature of 10°C and a humidity of 70%. The aged plastic clay was extruded into a cylindrical embryo through an extruder. The drying environment temperature was 30°C and the humidity was 70%, gradually changing from low temperature and high humidity to high temperature and low humidity. The drying time was 9 days. Calcination was carried out in a continuous mesh belt kiln, the calcination temperature was 530°C, the product kiln temperature was 70°C, and the roasting time was controlled at 48 hours. Finally, it was cut into 5mm cylinders according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions was obtained, which was recorded as CAT-5. After the catalyst was filled into the reactor, the reaction device was first purged with high-purity nitrogen for 20 hours; secondly, hydrogen was introduced, and the temperature was reduced in a step-by-step manner. The final reduction temperature was 550°C, and the reduction was 240 hours. The reaction gas ammonia was introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0033] Example 6 72.31kg of ruthenium trichloride and 12.11kg of ruthenium nitrate were dissolved in 150.0kg of water to form a mixed solution A; 102.46kg of praseodymium nitrate hexahydrate was dissolved in 120.0kg of distilled water to form a mixed solution B; 284.0kg of (111) magnesium oxide powder, 1.3kg of hydroxypropyl methylcellulose, and 0.5kg of polyvinyl alcohol were added to 63.24kg of deionized water and stirred at high speed for 30min; then the A solution was slowly added to the mixer and stirred at high speed for 45min; then the B solution, 2.2kg of glass fiber, 1.5kg of pulp fiber and 2.1kg of lactic acid were added and stirred at high speed for 45min; the remaining 426.0kg of (111) magnesium oxide powder and 106.32kg of distilled water were added again and stirred at high speed for 45min, and the water content was controlled at 35%. Finally, the plastic clay was obtained after filtration and vacuum kneading. The mixture was aged for 26h at a temperature of 18℃ and a humidity of 70%. The aged plastic clay is extruded into a cylindrical embryo through an extruder. The drying environment temperature is 30°C and the humidity is 70%. It gradually changes from low temperature and high humidity to high temperature and low humidity. The drying time is 9 days. The calcination adopts a continuous mesh belt kiln, the calcination temperature is 600°C, the product kiln temperature is 60°C, and the roasting time is controlled at 48h. Finally, it is cut into 3mm cylinders according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions is obtained, which is recorded as CAT-6. After the catalyst is filled into the reactor, the reaction device is first purged with high-purity nitrogen for 20h; secondly, hydrogen is introduced, and the temperature is reduced in a step-by-step manner. The final reduction temperature is 450°C, and the reduction is 220h. The reaction gas ammonia is introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0034] Example 7 33.6 kg of ruthenium trichloride was added to 70.0 kg of water to dissolve to form a mixed solution A; 69.78 kg of samarium nitrate hexahydrate and 45.36 kg of cobalt nitrate hexahydrate were dissolved in 130.0 kg of distilled water to form a mixed solution B; 4.36 kg of rubidium hydroxide was dissolved in 35.0 kg of distilled water to form a mixed solution C; 438.0 kg of (111)-face magnesium oxide powder, 1.1 kg of hydroxypropyl methylcellulose, 0.7 kg of carboxymethyl cellulose, 0.6 kg of polyethylene oxide and 0.7 kg of polyvinyl alcohol were added to 76.12 kg of deionized water and stirred at high speed for 35 minutes; then solutions A and B were slowly added to the mixer in turn and stirred at high speed for 45 minutes; then solutions C, 5.0 kg glass fiber, 1.0kg pulp fiber and 3.0kg lactic acid, stir at high speed for 30min; add the remaining 385.0kg (111) face magnesium oxide powder and 106.32kg distilled water again, stir at high speed for 30min, control the moisture at 35%, and finally obtain plastic clay after filtration and vacuum kneading. Aged for 30h in an environment with a temperature of 10℃ and a humidity of 70%. The aged plastic clay is extruded into a cylindrical embryo through an extruder. The drying environment temperature is 30℃ and the humidity is 70%, gradually changing from low temperature and high humidity to high temperature and low humidity. The drying time is 9 days. Calcination adopts a continuous mesh belt kiln, the calcination temperature is 550℃, the product kiln temperature is 65℃, and the roasting time is controlled at 48h. Finally, it is cut into 3mm cylinders according to the size requirements, that is, the catalyst for hydrogen production by decomposition of ammonia under mild conditions is obtained, which is recorded as CAT-7. After the catalyst was filled into the reactor, high-purity nitrogen was first used to purge the reaction device for 32 hours; then hydrogen was introduced, and the temperature was increased stepwise to reduce the catalyst, with the final reduction temperature being 540°C. After 200 hours of reduction, ammonia gas was introduced as the reaction gas to carry out hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0035] Example 8 24.32 kg of ruthenium nitrate and 21.36 kg of ruthenium chloride were dissolved in 100.0 kg of water to form a mixed solution A; 74.01 kg of ytterbium nitrate hexahydrate and 106.01 kg of ferric nitrate nonahydrate were dissolved in 230.0 kg of distilled water to form a mixed solution B; 5.61 kg of sodium sulfate was dissolved in 35.0 kg of distilled water to form a mixed solution C; 300.0 kg of (111)-faced magnesium oxide powder, 0.3 kg of hydroxypropyl methylcellulose, 0.6 kg of carboxymethyl cellulose, 0.8 kg of polyvinyl alcohol, 0. 1kg methyl methacrylate was added to 63.24kg deionized water and stirred at high speed for 30min; then solution A was slowly added to the mixer and stirred at high speed for 30min; then the mixed solution of B and C, 5.0kg glass fiber, 1.5kg pulp fiber and 3.0kg lactic acid were added and stirred at high speed for 30min; the remaining 450.0kg (111)-face magnesium oxide powder and 106.32kg distilled water were added again and stirred at high speed for 30min, and the moisture content was controlled at 28%. Finally, the plastic clay was obtained after filtration and vacuum kneading. Aged for 24h in an environment with a temperature of 10℃ and a humidity of 70%. The aged plastic clay was extruded into a Raschig ring embryo through an extruder. The drying environment temperature was 30℃ and the humidity was 70%, gradually changing from low temperature and high humidity to high temperature and low humidity. The drying time was 9 days. The calcination was carried out in a continuous mesh belt kiln, the calcination temperature was 500℃, the product kiln temperature was 70℃, and the roasting time was controlled at 48h. Finally, the catalyst was cut into 3 mm Raschig rings according to the size requirements, and the ammonia decomposition hydrogen production catalyst under mild conditions was obtained, which was recorded as CAT-8. After the catalyst was filled into the reactor, the reaction device was first purged with high-purity nitrogen for 20 hours; then hydrogen was introduced, and the temperature was increased step by step to reduce the final reduction temperature of 650 ° C. After 180 hours of reduction, the reaction gas ammonia was introduced to carry out the hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0036] Comparative Example 1 950.0kg industrial magnesium oxide powder and 1.0kg hydroxypropyl methylcellulose were added to 620.24kg deionized water and stirred for 30min; 102.59kg ruthenium trichloride was dissolved in 300.0kg water to form a solution, added to the above mixture, and stirred for 120min; mud was obtained. The mud was extruded into an embryo, dried and calcined. Finally, granulation was performed according to the size requirements to obtain catalyst particles, which were recorded as DB-1. After the catalyst was filled into the reactor, ammonia was introduced, and the temperature was increased for reduction. The final reduction temperature was 650℃, and the reduction was carried out for 180h. The reaction gas ammonia was introduced to carry out hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0037] Comparative Example 2 900.0kg industrial magnesium oxide powder and 1.5kg hydroxypropyl methylcellulose were added to 310.24kg deionized water and stirred for 45min; 63.46kg ruthenium trichloride and 247.73kg nickel nitrate hexahydrate were dissolved in 600.0kg water to form a solution, which was added to the above mixture and stirred for 90min; mud was obtained. The mud was extruded into an embryo, dried and calcined. Finally, granulation was performed according to the size requirements to obtain catalyst particles, which were recorded as DB-2. After the catalyst was filled into the reactor, hydrogen was introduced, and the temperature was increased for reduction. The final reduction temperature was 550℃, and the reduction was carried out for 200h. The reaction gas ammonia was introduced to carry out hydrogen production reaction. The ammonia decomposition efficiency of the catalyst is shown in Table 1.
[0038] Table 1 Ammonia decomposition efficiency of catalysts in Examples and Comparative Examples As can be seen from Table 1, the ammonia decomposition hydrogen production catalysts prepared in Examples 1-8 have significantly better ammonia decomposition efficiency than Comparative Examples 1 and 2. In the range of 400-600°C, the ammonia decomposition efficiency remains above 99%, and have excellent ammonia decomposition hydrogen production catalytic performance.
Claims
1. A catalyst for hydrogen production by decomposing ammonia under mild conditions, characterized in that: The mass percentages of the components in the catalyst are: MgO 55-99.87%, Ru 0.1-5% and SiO2 0.01-5%, and one or more of the following metal components: Me1 0.1-25% and Me2 0.02-10%.
2. A catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 1, characterized in that: The Me1 is one or more of lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, ytterbium, molybdenum, iron, cobalt and nickel, and the Me2 is one or more of lithium, sodium, potassium, rubidium and cesium.
3. A method for preparing a catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 1, characterized in that: The following steps are involved: (1) adding ruthenium salt to distilled water to dissolve to form solution A; the amount of ruthenium salt added is 0.1-5% of the total mass of the catalyst, measured by ruthenium; (2) dissolving at least one of a transition metal precursor and a rare earth metal precursor in distilled water to form a solution B; the amount of the metal precursor added is 0.1-25% of the total mass of the catalyst, measured by mass of metal Me1; (3) dissolving an alkali metal precursor in distilled water to form a solution C; the amount of the alkali metal precursor added is 0.02-10% of the total mass of the catalyst, measured by mass of metal Me2; (4) Add part of the (111)-face-rich octahedral magnesium oxide powder, a binder and a pore-forming agent into a mixer, add water, and stir at high speed for 3-60 minutes; then slowly add solution A into the mixer and stir at high speed for 10-120 minutes; then add at least one of solution B or solution C and a molding aid, and stir at high speed for 10-120 minutes; add the remaining octahedral magnesium oxide powder again, stir at high speed for 10-120 minutes, control the moisture content at 25-35%, and finally obtain a plastic clay after filtering and vacuum kneading, and then age it at a temperature of 10-30°C and a humidity of 60-70% for 24h-48h; extrude the aged plastic clay into a Raschig ring, a cloverleaf or a cylindrical embryo through an extruder, and obtain the ammonia decomposition hydrogen production catalyst after drying and calcining.
4. The method for preparing a catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 3, characterized in that: In step (1), the ruthenium salt is at least one of ruthenium trichloride or ruthenium nitrate.
5. The method for preparing a catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 3, characterized in that: In step (2), the transition metal precursor is at least one of a molybdenum salt, an iron salt, a cobalt salt and a nickel salt, and the rare earth metal precursor is at least one of a lanthanum salt, a cerium salt, a praseodymium salt, a neodymium salt, a samarium salt, a gadolinium salt and a ytterbium salt.
6. The method for preparing a catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 3, characterized in that: In step (3), the alkali metal precursor is at least one of a lithium salt, a sodium salt, a potassium salt, a rubidium salt and a cesium salt.
7. The method for preparing a catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 3, characterized in that: In step (4), the binder is at least one of hydroxypropyl methylcellulose, hydroxyethyl cellulose or carboxymethyl cellulose, and the amount used is 0.1-3% of the dry weight of the octahedral magnesium oxide powder; the pore-forming agent is at least one of polyethylene oxide, polyvinyl alcohol, methyl methacrylate or polystyrene, and the amount used is 0.1-2% of the total mass of the catalyst; the molding aids are glass fiber, pulp fiber and lactic acid, and the amounts used are 0.01-5%, 0.1-1.5% and 0.1-3% of the total mass of the catalyst, respectively.
8. The method for preparing a catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 3, characterized in that: In step (4), the drying environment temperature is 20-60°C, the humidity is 85-10%, and the temperature gradually changes from low temperature and high humidity to high temperature and low humidity. The drying time is 8-9 days. The calcination adopts a continuous mesh belt kiln, the calcination temperature is 300-650°C, the product outlet temperature is 60-80°C, and the roasting time is controlled at 40-48h.
9. Use of the catalyst for hydrogen production by decomposing ammonia under mild conditions as claimed in claim 1 in a hydrogen production reaction.
10. The use of the catalyst for hydrogen production by decomposition of ammonia under mild conditions in hydrogen production reaction as claimed in claim 9, characterized in that: The application method is as follows: after filling the ammonia decomposition hydrogen production catalyst into the reactor, first use an inert gas to completely purge and remove the oxygen in the reaction device and the catalyst pores; secondly, introduce a reducing gas: one of hydrogen or ammonia, and reduce the temperature in a step-by-step manner. The final reduction temperature is 400-650°C. The reduction time is related to the catalyst filling mass, generally 0.1~6 h / kg. After the reduction stage is completed, the reaction raw material gas: ammonia is introduced to carry out the hydrogen production reaction.
Citation Information
Patent Citations
Magnesium oxide-supported ruthenium catalyst for hydrogen preparation through ammonia decomposition, preparation method and applications thereof
CN108160072A
Ruthenium-based ammonia decomposition hydrogen production catalyst and preparation method and application thereof
CN109529865A
Nickel and / or ruthenium-based ammonia decomposition catalyst and preparation method and application thereof
CN110270338A
Applications of rare earth oxide loaded transition metal catalyst in ammonia decomposition reaction
CN111215086A
Ammonia decomposition hydrogen production catalyst and preparation method and application thereof
CN112337494A
Cited By
Monolithic catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of monolithic catalyst
CN121669281A
High-activity potassium ruthenium catalyst as well as preparation method and application thereof
CN122164400A